Vibration Analysis of the Drivetrain in Dependence on the Type of Gearbox Suspension Bushing - Jiri Struz; Lukas Hruzik; Jiri Havlik (Journal of Mechanical Engineering, 2021)
In the vast majority of technical applications, there is a necessity to transmit the torque from drive to driven machine together with the demand to overcome great distance between given devices. One of the solutions of this problem is the use of a cardan shaft. Operations of connecting shaft and drivetrain are accompanied by oscillations negatively influencing the driver comfort. Main subject of this article is the measurement of vibrations on different parts of a heavy truck and its evaluation by FFT analysis. Measurements are performed with two kinds of suspension bushing which are compared with to each other. Based on the previous measuring, influence of cardan shaft length was also investigated. First of all, dependency on the length of the cardan shaft on deflection angles for V arrangement was evaluated by analytical method. The theoretical introduction is followed by research of eigen frequency depending on the length of the cardan shaft. The results obtained by modal analysis in FEM are verified by experimental modal analysis [1].